2016
DOI: 10.1088/0034-4885/79/5/053901
|View full text |Cite
|
Sign up to set email alerts
|

Effective drifts in dynamical systems with multiplicative noise: a review of recent progress

Abstract: Noisy dynamical models are employed to describe a wide range of phenomena. Since exact modeling of these phenomena requires access to their microscopic dynamics, whose time scales are typically much shorter than the observable time scales, there is often need to resort to effective mathematical models such as stochastic differential equations (SDEs). In particular, here we consider effective SDEs describing the behavior of systems in the limits when natural time scales become very small. In the presence of mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
106
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(123 citation statements)
references
References 93 publications
2
106
0
Order By: Relevance
“…Note that rigorous results on the general symmetries of overdamped multiplicative white noise processes, clarifying some prevailing misconceptions on the Itô-Stratonovich dilemma and presenting an exact mapping of the different interpretations to a purely additive white noise process, were reported only recently 97 . Nevertheless, the notion of a ‘correct’ interpretation of multiplicative white noise Langevin equations is always context dependent 98100 , as it was shown, for example, that general non-linear relaxation processes not satisfying a fluctuation-dissipation theorem in fact obey a Fokker-Planck equation following from the Itô interpretation of the underlying Langevin equation 101 . Moreover, as we here advocate the general importance of higher-order statistics in the quantification of stationary and/or ergodic properties of single-particle time series data, the specific interpretation of the multiplicative white noise Langevin equation is not critical.…”
Section: Resultsmentioning
confidence: 99%
“…Note that rigorous results on the general symmetries of overdamped multiplicative white noise processes, clarifying some prevailing misconceptions on the Itô-Stratonovich dilemma and presenting an exact mapping of the different interpretations to a purely additive white noise process, were reported only recently 97 . Nevertheless, the notion of a ‘correct’ interpretation of multiplicative white noise Langevin equations is always context dependent 98100 , as it was shown, for example, that general non-linear relaxation processes not satisfying a fluctuation-dissipation theorem in fact obey a Fokker-Planck equation following from the Itô interpretation of the underlying Langevin equation 101 . Moreover, as we here advocate the general importance of higher-order statistics in the quantification of stationary and/or ergodic properties of single-particle time series data, the specific interpretation of the multiplicative white noise Langevin equation is not critical.…”
Section: Resultsmentioning
confidence: 99%
“…Smyshlyaev and Chen applied a position-dependent diffusion coefficient to the boundary feedback control of a diffusive system and proved the Mittag-Leffler stability of the system [45,46]. Several other works have since focussed on position-dependent diffusive systems [47][48][49][50], to name but a few.Differing from a constant diffusion coefficient, the presence of a position-dependent diffusivity involves the problem of how to interpret multiplicative noise in a stochastic equation, particularly, a noise-induced drift, which varies by choosing different integral forms, such as Itô, Stratonovich and isothermal integrals [44,51]. It is found that the probability distribution generated within the isothermal integral formulation effects the required Boltzmann distribution, which is correct in thermal equilibrium state [48][49][50], while the Itô and Stratonovich integrals lead to 'athermal' forms.…”
mentioning
confidence: 99%
“…It is found that the probability distribution generated within the isothermal integral formulation effects the required Boltzmann distribution, which is correct in thermal equilibrium state [48][49][50], while the Itô and Stratonovich integrals lead to 'athermal' forms. Generally, the Itô interpretation is employed in economics and biology due to their features of being 'only related to the latest past'; the Stratonovich integral finds applications in physical systems, such as electrical circuits driven by multiplicative noises (see [51], and references therein). In particular, it finds that with decreasing the mass of particles a second-order Langevin equation can reduce to a first-order one with different noise-induced drifts, depending on the relationship between friction and diffusion coefficients [51][52][53].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For a discussion of stochastic differential equations the reader may refer to a recent report on progress [112].…”
mentioning
confidence: 99%